2011
DOI: 10.1111/j.1465-3362.2011.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress-coping morbidity among family members of addiction patients in Singapore

Abstract: Subjective appraisal of stress and coping responses are essential factors affecting the morbidity of family members. Family members demonstrated a need and willingness to engage in formal treatment/counselling for their own problems that were attributed to living with an addiction patient. This provides an opportunity for stress management and brief interventions to modify coping styles, thereby minimizing the potential negative mental health impact on family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 25 publications
2
30
0
9
Order By: Relevance
“…One such study was conducted in Singapore and assessed spouses of males in treatment for alcohol dependence. They found similar results, with spouses of those with alcohol dependence having higher rates of depression, psychiatric morbidity and stress along with lower scores on physical and psychological well-being [3]. Moos et al conducted a study on older adults but found similar results, that is, spouses of those men who continued drinking had greater depression and poorer overall health when compared with spouses of men who never drank as well as those men who had stopped drinking several years back [10].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…One such study was conducted in Singapore and assessed spouses of males in treatment for alcohol dependence. They found similar results, with spouses of those with alcohol dependence having higher rates of depression, psychiatric morbidity and stress along with lower scores on physical and psychological well-being [3]. Moos et al conducted a study on older adults but found similar results, that is, spouses of those men who continued drinking had greater depression and poorer overall health when compared with spouses of men who never drank as well as those men who had stopped drinking several years back [10].…”
Section: Discussionmentioning
confidence: 86%
“…This leads to a situation where alcohol use disorder is a significant health problem in our country. This condition has wide-ranging consequences not only for the one who drinks, but also for their entire family [2,3]. A wide range of psychiatric problems has been reported in wives of patients with alcohol dependence, with mood and anxiety disorders being predominant, along with decreased marital satisfaction [2].…”
Section: Introductionmentioning
confidence: 99%
“…PSS, has yet to be validated in Singapore, it has been validated in several countries (32,50) and used in Singapore for different populations. (51,52) Lack of comprehensive information on exposure to tobacco smoke, as well as alcohol and caffeine intake did not allow for quantification and detailed examination of the association of these variables with the risk of miscarriage. As previously discussed, the presence of nausea and PSS ≥ 17 was associated with a decreased likelihood of complete miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…Diese führen dazu, dass sich das Risiko für die Angehörigen erhöht, selbst psychisch oder psychosomatisch krank zu werden (Lee, Manning, Teoh, Winslow, Lee, Subramaniam et al, 2011;Oreo & Ozgul, 2007;Orford et al, 1998c;Ray, Mertens & Weisner, 2007). So weisen Angehörige ein höheres Risiko auf, eine depressive Störung oder selbst eine Abhängigkeitserkrankung zu entwickeln (Lee et al, 2011;Ray et al, 2007).…”
Section: Introductionunclassified
“…Auf diese wird in den nächsten Kapiteln näher eingegangen. Es ist zudem erwiesen, dass die Belastungen, die durch die Abhängigkeit einer nahestehenden Person entstehen, auch Auswirkungen auf die Gesundheit der Angehörigen hat (Lee et al, 2011;Oreo & Ozgul, 2007;Orford et al, 1998c;Ray et al, 2007) (Orford et al, 1998c), wählten andere einen theoretischen Zugang (Kirby et al, 2005). Nachfolgend werden die Belastungen vorgestellt, die Angehörige im Zusammenhang mit der Suchterkrankung eines ihnen nahestehenden Menschen erleben können.…”
Section: Introductionunclassified